Extracellular vesicle long RNA markers of early‐stage lung adenocarcinoma. Issue 7 (15th December 2022) - Zhang, Yanwei; Liu, Wei; Zhang, Hongdao; Sun, Beibei; Chen, Tianxiang; Hu, Minjuan; Zhou, Haisheng; Cao, Ying; Han, Baohui; Wu, Ligang
Abstract: Lung cancer screening by low‐dose computed tomography (LDCT) can improve mortality rates among high‐risk individuals, especially adenocarcinoma cases with characteristically poor prognosis, although high false‐positive rates have limited its clinical application. The objective of our study was to identify biomarkers for early‐stage lung adenocarcinoma (ie, tumor diameter <2 cm) through extracellular vesicle long RNA (evlRNA) sequencing. High throughput evlRNA sequencing and support vector machine (SVM) identification of candidate diagnostic marker transcripts were performed using serum samples obtained before lung surgery. A total of 145 upregulated and 363 downregulated differential genes ( P value <.05, fold change >1.5) were identified between lung adenocarcinoma (LUAD) patients and benign controls. An SVM model based on a 23‐gene signature could distinguish EV samples of LUAD patients from those of control subjects with 86.49% sensitivity, 95.00% specificity and 92.31% accuracy in the training set and 93.75% sensitivity, 85.71% specificity and 88.24% accuracy in the validation set. A 17‐gene signature was then identified that could distinguish AIS patient samples from those of MIA/IAD patients with 93.33% sensitivity, 98.00% specificity, and 96.25% accuracy in the trainingset and 83.33% sensitivity, 96.55% specificity, and 94.29% accuracy in the validation set. EvlRNAs in serum show considerable diagnostic value for screening LUAD patients with tumor sizes <2 cm in conjunction with LDCT, potentially reducing false positive rates while improving mortality rates. Abstract : What's new? Low‐dose computed tomography (LDCT) can reduce lung cancer mortality in high‐risk groups, owing to early‐stage tumor detection. LDCT, however, also has relatively high false‐positive rates. The present study assessed the value of sequencing extracellular vesicle long RNAs (evlRNAs), which are enriched in the blood of lung cancer patients, as a supplementary tool to LDCT‐based lung cancer screening. High throughput screening and support vector machine analyses identified a 23‐gene evlRNA sequencing panel with high diagnostic value for early‐stage lung adenocarcinoma with tumors smaller than 2 cm. Incorporation of evlRNA sequencing into LDCT could help reduce false‐positive rates in lung cancer screening.